Modelling Inflation in the Euro Area - Eilev S. Jansen (Norges Bank, 2004)
The paper presents an incomplete competition model (ICM), where inflation is determined jointly with unit labour cost growth. The ICM is estimated on data for the Euro area and evaluated against existing models, i.e. the implicit inflation equation of the Area Wide model (AWM) - cf. Fagan, Henry and Mestre (2001) - and estimated versions of the (single equation) P* model and a hybrid New Keynesian Phillips curve. The evidence from these comparisons does not invite decisive conclusions. There is, however, some support in favour of the (reduced form) AWM inflation equation. It is the only model that encompasses a general unrestricted model and it forecast encompasses the competitors when tested on 20 quarters of one step ahead forecasts.
hdl:11250/2498543; Additional information: This paper is a revised version of ECB Working Paper No. 322 (Jansen (2004)), which is prepared for presentation at the Econometric Society European Meeting in Madrid 20.-24. August 2004. It was written as part of the project "Modelling wages and prices in the Euro area", while the author was a Research Visitor to DG Research, European Central Bank, Frankfurt from February through June 2003. Parts of the paper will be published in The Econometrics of Macroeconomic Modelling, forthcoming in the series Advanced Texts in Econometrics from Oxford University Press (Bårdsen et al. (2004a)). I am grateful to Øyvind Eitrheim for his permission to include unpublished material from Eitrheim and Jansen (2003). While working on this project, I have received valuable data assistance from Elena Angelini and Alistair Dieppe of DG Research as well as from Mika Tujula and Focco Vijselaar of DG Economics at the ECB. An anonymous ECB referee has provided helpful advice and comments from Christopher Bowdler, Gabriel Fagan, David Hendry, Jérôme Henry, Ricardo Mestre, Ragnar Nymoen and seminar participants at the ECB, Norges Bank, Norwegian University of Science and Technology, and University of California San Diego are also gratefully acknowledged. The views expressed in this paper represent exclusively the views of the author and do not necessarily reflect those of the European Central Bank or Norges Bank.
Keywords: C22; C32; C52; C53; E31; 330; Area Wide model; P*-model; New Keynesian Phillips curve; inflation; incomplete competition model; model evaluation; forecast encompassing